Community approach for reducing small field measurement errors: Experience over 24 centres. (March 2019) - Talamonti, Cinzia; Russo, Serenella; Pimpinella, Maria; Falco, Maria Daniela; Cagni, Elisabetta; Pallotta, Stefania; Stasi, Michele; Mancosu, Pietro
Abstract: Purpose: The complexity of the modern Stereotactic Body Radiation Therapy (SBRT) techniques requires comprehensive quality assurance programs, to ensure the right treatment to the patient. Dosimetry of small radiation fields is a challenge especially for radiotherapy centres starting to work on this issue. The matter to be discussed here concerns the need of detailed measurement procedures and cross checks to be paired to the usual recommendations on detectors and correction factors. Materials and Methods: The presented work involved 24 Italian radiotherapy centres, with the specific purpose to minimize systematic errors in output factor measurements over different radiotherapy centres. Using the unshielded silicon diode IBA Razor, reference curves for the relative signal ratio (RSR) as a function of beam size were created for each Linac family. Results: With this study we have demonstrated consistency of small field dosimetry on all the centres involved, moreover all radiotherapy centres using Razor are allowed to compare measurements amongst each other and centres with values deviating more than 5% from the reference curve are advised to repeat their measurements. With this procedure, some critical issues were detected from two centres in RSR measurements, that, if implemented into the own treatment planning system, would induce an unwanted overdosage larger than 5%. Conclusions: The proposed approach could allow one to envision high-skilled therapy centres providing support to those featuring minor experience and could represent an important strategy for the clinical implementation of emerging technologies at high quality levels. The methodology adopted exploits crowd knowledge methods which could be applied in others areas of radiation dosimetry.